Gene Mutational Clusters in the Tumors of Colorectal Cancer Patients With a Family History of Cancer - Huang, He; Deng, Ting; Guo, Yuntong; Chen, Hao; Cui, Xiaolong; Duan, Jingjing; Yang, Yuchong; Guo, Zhixin; Ba, Yi (Frontiers in Oncology, 2022)
Introduction Family history is a high-risk factor for colorectal cancer (CRC). The risk comes not only from known germline mutations but also from the other family-related mechanisms. Uncovering them would be an important step to improve the diagnosis and treatment of these patients. Method Samples from 168 patients with advanced CRC were collected and applied to next-generation sequencing of 624 pan-cancer genes. Genomic mutations and significantly mutated genes were identified. Significantly mutated genes and co-mutated genes were used to cluster patients. For each cluster of patients, mutational signatures were extracted. The identified mutational signatures were further validated in the other independent cohort. Result Significantly mutated genes including TP53, APC, KRAS, and SMAD4 were found associated with tumor mutational burden and microsatellite instability. LRP1, ACVR2A, and SETBP1 were found co-mutated. Patients with mutations in LRP1, ACVR2A, and SETBP1 tend to have a family history of cancer. Those patients tended to have right-sided tumors with high tumor mutational burden and microsatellite instability. Among them, signature analysis identified two possible etiologies, SBS10a (defective polymerase epsilon exonuclease domain) and SBS6 (defective DNA mismatch repair and microsatellite unstable tumors). These signatures were also found in another independent cohort. Conclusion The gene cluster (LRP1, ACVR2A, and SETBP1) could be a good biomarker of these patients with a family risk, which was characterized by right-sidedness, high tumor mutational burden, and high microsatellite instability.